The Role of Implicit and Explicit Staff Attitudes in the Use of Coercive Measures in Psychiatry - Vandamme, Angelika; Wullschleger, Alexandre; Garbe, Amelie; Cole, Celline; Heinz, Andreas; Bermpohl, Felix; Mielau, Juliane; Mahler, Lieselotte; Montag, Christiane (Frontiers in Psychiatry, 2021)
Many determinants leading to the use of different coercive measures in psychiatry have been widely studied and it seems that staff attitudes play a crucial role when it comes to the decision-making process about using coercion. However, research results about staff attitudes and their role in the use of coercive measures are inconsistent. This might be due to a focus on self-report studies asking for explicit answers, which involves the risk of bias. This study aimed to expand research on this topic by examining the impact of explicit and implicit staff attitudes on the use of coercive measures in clinical practice. In addition, the influence of gender, profession (nurses, psychiatrists) and years of professional experience as well as their influence on staff attitudes were examined. An adaption of the implicit association measure, the Go/No-Go Association Task (GNAT), with the target category coercion and distracter stimuli describing work load, as well as the explicit questionnaire Staff Attitudes to Coercion Scale (SACS) was completed by staff (N=149) on 13 acute psychiatric units in 6 hospitals. Data on coercive measures as well as the total number of treated cases for each unit was collected. Results showed that there was no association between staff’s implicit and explicit attitudes towards coercion, and neither measure was correlated with the local frequency of coercive measures. ANOVAs showed a significant difference of the GNAT result for the factor gender (F=9.32 p=0.003), demonstrating a higher tendency to justify coercion among female staff members (M=-0.23, SD=±0.35) compared to their male colleagues (M=-0.41, SD=±0.31). For the SACS, a significant difference was found for the factor profession (F=7.58, p=0.007), with nurses (M=2.79, SD=±1.40) showing a more positive attitude to the use of coercion than psychiatrists (M=2.15, SD=±1.11). No significant associations were found regarding the extent of professional experience. Results indicate a complex interaction between implicit and explicit decision-making processes dependent on specific contexts. We propose future research to include primers for more context-related outcomes. Furthermore, differences in gender suggest a need to direct attention towards occupational safety and possible feelings of anxiety in the workplace, especially for female staff members.